2016
DOI: 10.1017/jfm.2016.425
|View full text |Cite
|
Sign up to set email alerts
|

Bubbly shock propagation as a mechanism for sheet-to-cloud transition of partial cavities

Abstract: Partial cavitation in the separated region forming from the apex of a wedge is examined to reveal the flow mechanism responsible for the transition from stable sheet cavity to periodically shedding cloud cavitation. High-speed visualization and time-resolved X-ray densitometry measurements are used to examine the cavity dynamics, including the time-resolved void-fraction fields within the cavity. The experimentally observed time-averaged void-fraction profiles are compared to an analytical model employing free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
170
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(190 citation statements)
references
References 32 publications
19
170
1
Order By: Relevance
“…It should be noted that during the propagation of shock wave, there exists sharp decrease in void fraction at the shock front, while during the development of re-entrant flow, no evident void fraction change is found. The sharp decrease in void fraction within the cavity will significantly change the cavity dynamics through changing the local speed of sound, and thus the local Mach number [21]. The propagation speed of the shock wave within the attached cavity based on both the high-speed video and the averaged gray level contour is estimated to be 7.12 m/s.…”
Section: Experiments Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that during the propagation of shock wave, there exists sharp decrease in void fraction at the shock front, while during the development of re-entrant flow, no evident void fraction change is found. The sharp decrease in void fraction within the cavity will significantly change the cavity dynamics through changing the local speed of sound, and thus the local Mach number [21]. The propagation speed of the shock wave within the attached cavity based on both the high-speed video and the averaged gray level contour is estimated to be 7.12 m/s.…”
Section: Experiments Setupmentioning
confidence: 99%
“…To confirm the characteristics of the shock wave, the one-dimension bubbly shock wave relationship is applied. Ignoring the bubble dynamics of the shocking process, the speed upstream of the discontinuity in the reference frame of the shock is obtained in eqn (9) [21]. ,…”
Section: Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion of the re-entrant liquid jet is central to the periodic shedding of the cavitation cloud, but the mechanism that drives the phenomenon is still not fully known [54]. It has been observed [60] that the re-entrant jet is dominant during the earlier stages of the instability, whereas a propagating shock wave appears during the later stages for the intensive cloud-shedding phase [61].…”
Section: Different Hydrodynamic Cavitation Regimes In Nozzlesmentioning
confidence: 99%
“…For example, the experiments of Reisman et al [1] showed that condensation shocks cause large pressure spikes which influence the behaviour of sheet cavities (e.g. [2,3]), and recent work has demonstrated that condensation shocks are responsible for the transition from stable to cloud-shedding cavities [4].…”
Section: Introductionmentioning
confidence: 99%